Karakteristik Perolehan Angka Permainan Sepak Takraw Nomor Double Event Pada POMNAS 2022 Di Sumatera Barat - Daud Pramudita W; Abdul Aziz H; Heri Wahyudi; Mokhamad Nur Bawono (Universitas Maritim AMNI Semarang, 2024)
The development of sepak takraw originates from a traditional game that originally developed in North Sumatra, West Sumatra, South Sumatra. This sepak takraw game has various names for this type of game in various regions, such as the famous one in Riau, namely high rago, in Bengkulu it is called Cepak, in Sumatra and Jambi it is called sapak rago, while in South Sulawesi it is known as Marraga - Akraga. South Sulawesi, North Sumatra, South Sumatra and West Sumatra are places that produce rattan which will be used as raw material for making takraw balls. Double event sepak takraw is a sepak takraw game played by two people in one team, the way of playing is slightly different from the general sepak takraw game. The difference is that the serve is generally carried out in a ditekong or half circle for the ball thrower and also a circle in the middle of each team's area which has the function of kicking the initial ball which is often called a serve but in this study a double event game is used where the serve is done alone so that the kicker or throwing is done alone.